Comparing the effectiveness of Acceptance and Commitment Therapy (ACT), Cognitive Behavioral Therapy (CBT) and Mindfulness on body image concerns of overweight patients - Rashidi Zafar, Maryam; Bashardost Tajali, Fariba; Sharifi, Nastaran (Journal of Personality and Psychosomatic Research (JPPR), 2023)
This study aimed to compare the effectiveness of acceptance and commitment therapy (ACT), cognitive behavioral therapy (CBT) and mindfulness on body image concerns of overweight patients. The method was a quasi-experimental type with a pre-test and post-test design with a control group. The statistical population of this study included all overweight women (body mass index between 25 and 29.9) in Varamin City. In the present study, 80 women were considered as the sample size. The sampling method in the present study was done voluntarily. Sampling was done over two months by calling overweight people living in Varamin City. Then, 80 of them were selected by lottery and, after matching, were placed in 4 groups. Then, psychotherapeutic interventions were performed on the experimental group members, while the control group did not receive any intervention. Littleton's (2005) Body Image Concern Inventory was used to collect data. In order to statistically analyze the data, analysis of covariance and Bonferroni's post hoc test and SPSS software were used. The univariate analysis of covariance showed a difference between concern about the body image of the control group, with cognitive-behavioral therapy, therapy based on acceptance and commitment, and mindfulness in overweight people. Also, the results of the Bonferroni post-hoc test showed that all three interventions effectively reduced body image concerns, but there was no significant difference between the test groups.